Configurational theory and methods in organizational research - Fiss, Peer C.; Cambré, Bart; Marx, Axel (Emerald, 2013)
Some 20 years after the emergence of configurational theory as a key perspective in organization studies in the 1990s, this approach has yet to deliver on its promise. While we know that configurations the relative arrangement of parts and elements - matters, empirical research on configurations is just beginning to deliver on its promise. The starting point of the edited volume is the revival and evolution of a configurational perspective on organizations, both in terms of the use of configurational set-theoretic methods such as Qualitative Comparative Analysis (QCA) and in terms of configurational theorizing that has emerged from the use of such methods. The volume brings together a variety of scholars working with set theoretic configurational methods to apply these methods to a range of prominent fields in organization studies, ranging from organizational design, international business, and human resource practices to networks and the management of information systems. Each author or group of authors pays specific attention to assessing the potential of set-theoretical configurational methods for organization studies. Two extensive introductory chapters discuss the state of the art with regard to different set-theoretic (fuzzy set and crisp set) methods. In three response pieces leading scholars offer a reflection on the potential of set-theoretic methods for organizational analysis. The volume aims to provide both inspiration and practical advice on how to conduct configurational analysis. The chapters illustrate the breadth of organizational fields and the growing range of topics for which the configurational perspective can provides insights. This volume vividly illustrates that the configurational approach is maturing. It aims to inspire organizational scholars to develop theories and methods that truly consider organizations as clusters of interconnected structures and practices that have to be studied as configurations.
Keywords: Organizational behavior -- Research -- Methodology.; elektronické knihy; electronic books